Preliminary evaluation of meloidogyne incognita race 3 reproduction on garden pea cultivars in Brazil/ Avaliação preliminar da reprodução de Meloidogyne incognita raça 3 em cultivares de ervilha no Brasil - Luiz Carlos Camargo Barbosa Ferraz; Ana Cristina Magalhães Araújo; Carlos Eduardo Rossi (Semina: Ciências Agrárias, 2000)
Thirteen garden pea cultivars, were assessed for the reproductive rate of the root-knot nematode Meloidogyne incognita race 3 under greenhouse conditions. Two-week old plants growing were inoculated with 5.000 eggs. The nematode reproduction data was determined 55 days later according to the three adopted evaluation criteria (root-gall and egg-mass indexes, reproduction factor, percentage of reduction of the reproduction factor in relation to the susceptible standard cultivar). The tested cultivars were rated as highly susceptible ('Trolly'. 'Jurema'), susceptible ('Luiza'. 'Mini'. 'Asterix', 'Verde Temprana') or moderately susceptible ('Marina', 'Telephone'., 'Dileta'. 'Bolero', 'Flávia'. 'Viçosa', and 'Maria') hosts for the nematode. Avaliaram-se as taxas reprodutivas e caracterizaram-se as reações de 13 cut tiveres de ervilha em relação ao nematóide de galhas Meloidogyne incognita raça 3, em casa-de-vegetação. Plantas com duas semanas de idade, foram inoculadas com 5000 ovos do nematóide. As avaliações foram realizadas após 55 dias com base nos critérios - índices de galhas/índices de massas de ovos, fator de reprodução e porcentagem de redução do fator de reprodução. Duas cultivares foram consideradas hospedeiras altamente suscetíveis (‘Trolly’, ‘Jurema’), cinco suscetíveis ('Luíza', 'Mini', 'Asterix', 'Verde Temprana', 'Telefone') e seis moderadamente suscetíveis ('Marina'. 'Dileta', 'Boiero'. 'Flávia'. 'Viçosa', 'Maria').